2004
DOI: 10.1111/j.1601-0825.2004.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

T102C polymorphism of the 5‐HT2A receptor gene may be associated with temporomandibular dysfunction

Abstract: The T102C polymorphism may be involved in the etiology of temporomandibular dysfunction. The overrepresentation of the C/C variant of 5-HT2A receptor gene in temporomandibular dysfunction suggests a possible role of the serotonergic system in this disease, particularly at the receptor level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Overrepresentation of the C/C variant of the 5-HT2A receptor gene was found in temporomandibular dysfunction suggesting a possible role of the serotonergic system in this disease as well [33]. Juhasz and colleagues have suggested that genetic susceptibility to migraine may be associated with a locus at or near the 5-HT transporter gene [34].…”
Section: Irritable Bowel Syndrome Geneticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Overrepresentation of the C/C variant of the 5-HT2A receptor gene was found in temporomandibular dysfunction suggesting a possible role of the serotonergic system in this disease as well [33]. Juhasz and colleagues have suggested that genetic susceptibility to migraine may be associated with a locus at or near the 5-HT transporter gene [34].…”
Section: Irritable Bowel Syndrome Geneticsmentioning
confidence: 97%
“…The C/C genotype over represented in patients; T/T genotype over represented in controls [33] Migraine future science group future science group the 5-HT transporter (5-HTT) regulates the duration and strength of interactions between 5-HT and its receptors. A polymorphism within the 5-HTT 5´ upstream region (5-HTTLPR) has been reported, of which the majority is composed of either 14 (S) or 16 (L) repetitive elements.…”
Section: Fms Patientsmentioning
confidence: 99%
“…Studies of the HTR2A have also consistently shown that the silent 102T > C polymorphism is associated with an increased risk of both FMS [9,22] and TMJD [23].…”
Section: Serotoninergic Candidate Genesmentioning
confidence: 98%
“…For a long time it has been known that 5-HT2 A receptors activate the phospholipase C-β second messenger pathway,1 and 5-HT2 A receptors triggered a rapid and transient tyrosine phosphorylation of Jak2 kinase in response to serotonin 3. In addition, previous studies have shown an association between the rs6313 (T102C polymorphism) of HTR2A and diseases with musculoskeletal manifestations, ie, fibromyalgia4 and temporomandibular dysfunction 5. Furthermore, a recent study showed that patients with rheumatoid arthritis (RA) had a decreased B max of 5-HT2 A receptors compared with age- and sex-matched controls 6.…”
mentioning
confidence: 99%